Sweet and hot: the lovers spice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
In an attempt to diversify their agriculture and find niche markets to increase exports, several Pacific countries including Fiji, Samoa and Vanuatu are betting on the cultivation of ginger (Zingiber officinale). The world s largest producers are...